Effect of am fungi, azospirillum brasilense and pseudomonas fluorescence on growth, biomass, nutrient uptake, and yield enhancement in cultivar byadagi kaddi of capsicum annuum l. - JYOTI PUTTARADDER; H. C. LAKSHMAN (International Journal of Pharma and Bio Sciences, 2017)
The interactions of rhizosphere microbes among plants depend on the establishment of intimate associations connecting the two partners. Green house experiments were undertaken between beneficial microbes Azospirillum brasilense, Pseudomonas fluorescence, with AM fungus (Rhizophagus fasciculatus) on cultivar Byadagi kaddi of Capsicum annuum L. The results revealed that plant growth, biomass, fruit yield and nutrient uptake and mycorrhizal spore number and per cent root colonization were significantly additive response in triple inoculation over the control or non inoculated plants. However, dual or single inoculations brought better response over the control plants. Over all the maximum benefits were offered by the inoculation of AM fungus (Rhizophagus fasciculatus) with Azospirillum brasilense and Pseudomonas fluorescence was recorded. The varied response in cultivar Byadagi kaddi of Capsicum annuum L. with three bioinoculants and their synergistic importance have been discussed.